Modeling the Impact of Awareness and Environmental Sanitation on Typhoid Fever Transmission - Olumuyiwa James Peter; Sharifah Ahmad; Janet O. Agbaje; Festus Abiodun Oguntolu; Zainab Olabisi Dere; Olasubomi Abdulateef Bakare; Dipo Aldila (Department of Mathematics, Universitas Negeri Gorontalo, 2026)
Typhoid fever has been a significant burden even now in many poorer countries, mainly because of poor sanitation, contaminated water supplies, and the steady steady stream of asymptotic carriers who incessantly contaminate the environment. In this paper, we propose and analyze a compartmental model incorporating these aspects along with awareness-induced behavioral changes. The model has compartments for the susceptible population, the carriers, the infectious population who show symptoms, those who have recovered from the disease, a separate compartmenting the quantity of Salmonella Typhi in the environment. The infection spreads largely because of the intake of contaminated food and water. It adopts a nonlinear saturation incidence function describing the reduced possibility of infection with elevated contact rates. An awareness factor diminishes the probability of infection. It determines the basic reproduction number. It also demonstrates the disease-free equilibrium being globally stable. A locally stable endemic equilibrium has also been determined. A PRCC analysis has identified awareness, sanitation standards, the strength of infection transfer, and the bacterial shedding rates as the dominating parameters influencing the dynamics. Numerical examples validate the above theoretical studies. It has been observed that increased awareness along with improved sanitation practices substantially reduce the extent of the spread of the disease. Most importantly, the combined effects of behavioral modification along with enhanced sanitation practices have the potentially most profound effects on the reduction of the extent of the disease.